Aicardi Syndrome – A Rare Case Report - Bindhu.S2, Sumanth Shetty3, Dhanesh Kumar K U1, (Recent Research in Science and Technology, 2011)
Aicardy syndrome is a rare genetic disorder identified by French Neurologist ,Dr.Jean Aicardy in 1965.The number of identified cases of children with Aicardy syndrome is very difficult to assess accurately, and it affects only females and in very rare cases ,males with Klinefelters syndrome. Aicardy syndrome is characterized by the absence of corpus callosum, either partial or complete, infantile spasms, lesions or lacunae of the retina of the eye that are very specific to this disorder, microcephaly, and procencephalic cysts. We present a case report of Aicardy syndrome which has come to our hospital OPD, the patient was 7 year old girl, having severe spasm during flexion, and scoliosis. The patient was mentally retarded, with a dental abscess, and cleft palate. Once the patient was identified with Aicardy syndrome, she has subjected to detailed evaluation for other abnormalities.